Getting by in Europe's Urban Labour Markets Senegambian Migrants' Strategies for Survival, Documentation and Mobility - Van Nieuwenhuyze, Inge (IMISCoe Dissertations, 2008)
This book examines two major social changes experienced by European cities in the last two decades: post-industrial economic restructuring and new immigration flows. The link between both has been extensively discussed throughout a variety of theoretical approaches and in numerous descriptive contributions. Adding to those studies, this research focuses on three elements of migratory experience that have been relatively neglected thus far: a dynamic view of changes over time, the influence of national welfare and legislation frameworks, and the importance of support mechanisms outside the labour market. The material underpinning the arguments is the qualitative life-course analysis of 81 in-depth interviews with Senegambian migrants living in Antwerp and Barcelona.